HAK POLITIK INDIVIDUAL PRA DAN PASCA MENJADI NARAPIDANA DALAM SISTEM KETATANEGARAAN - Agus Salim; Asip Suyadi (Program Studi Hukum Universitas Pamulang, 2020)
Indonesia is a democratic country. Every citizen has political rights guaranteed by the 1945 Constitution of the Republic of Indonesia.Protection of political rights as a human right owned by every citizen. Protection of citizens' political rights or individual political rights contained in the 1945 Constitution, namely Article 27 paragraph (1) states the equality of all citizens towards law and government; Article 28 concerning freedom; Article 28D paragraph (1) concerning the right to recognition, guarantee, protection and legal certainty for everyone; Article 28D paragraph (3) states that every citizen has the right to obtain equal opportunities in government; and Article 31 paragraph (1) to obtain education. Democracy occurs if there is recognition of political rights and the implementation of political participation of every citizen. Fulfillment of political rights before and after the prisoners also receive protection of their political rights. The political rights of ex-prisoners are protected by the constitution of the 1945 Constitution, Law Number 39 of 1999, and Law Number 7 of 2017 concerning General Elections, and Constitutional Court Rejection Number 4 / PUU-VII / 2009. Based on this matter, this study aims to find out and analyze individual political rights that are confiscated along with the execution of punishment, and to know and analyze individual political rights to be able to conduct themselves after inmates. This research is descriptive analytical with a normative juridical approach.